Research on the Interactive Relationship between Industrial Structure Upgrading and Economic Growth in Qinghai Province—Empirical Analysis Based on the VAR Model - Geng, Qiangyan; Qi, Dengju; Hu, Xiwu (Journal of Theory and Practice in Economics and Management, 2025)
There has long been an inseparable relationship between industrial structure and economic growth. On the basis of data from 1978–2021, this paper uses the VAR model to study and analyze the interactive relationship between industrial structure upgrading and economic growth in Qinghai Province. Since the reform and opening up, the optimization and upgrading of the industrial structure in Qinghai Province have been unsatisfactory, and the role of industrial structure upgrading in promoting economic growth has not been prominent. There is a long-term and stable equilibrium relationship between the upgrading of the industrial structure and economic growth in Qinghai Province, and there is an interaction between the upgrading of the industrial structure and economic growth. In the short term, the promotion of the industrial structure by the first and second industries will continue, and the impact of the tertiary industry on the industrial structure has a significant driving effect, but the process is relatively slow, and the impact of the industrial structure upgrading on the three major industries has an obvious slow and lasting lag effect.